POST COVID: WHAT LESSONS CAN BE LEARNED FOR THE BANKING AND MSME INDUSTRY - Aripin, Zaenal; Agusiady, Ricky; Saepudin, Didin (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2023)
The COVID-19 pandemic has had a significant impact on global business dynamics, especially in the banking industry and Micro, Small and Medium Enterprises (MSMEs). Changes in consumer behavior, economic uncertainty, and supply chain disruption demand rapid adaptation and innovation. Therefore, this study aims to explore lessons learned from post-COVID-19 experiences and apply them in the context of the banking industry and MSMEs. This research aims to identify key lessons that can be drawn from the post-COVID-19 experience and analyze the impact on the strategy and sustainability of the banking industry and the development of MSMEs. This research uses descriptive qualitative methods by conducting in-depth case studies of several banking institutions and MSMEs that have experienced significant changes after COVID-19. Data collection was conducted through interviews, document analysis, and participatory observation. This research resulted in an in-depth understanding of the impact of COVID-19 on the banking industry and MSMEs, as well as the identification of key lessons. It found that adaptability, cross-sector collaboration, digital transformation, and adaptive risk management are crucial elements for the future success and sustainability of these two sectors.